(6+w)(5w+3)=0

Simple and best practice solution for (6+w)(5w+3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6+w)(5w+3)=0 equation:


Simplifying
(6 + w)(5w + 3) = 0

Reorder the terms:
(6 + w)(3 + 5w) = 0

Multiply (6 + w) * (3 + 5w)
(6(3 + 5w) + w(3 + 5w)) = 0
((3 * 6 + 5w * 6) + w(3 + 5w)) = 0
((18 + 30w) + w(3 + 5w)) = 0
(18 + 30w + (3 * w + 5w * w)) = 0
(18 + 30w + (3w + 5w2)) = 0

Combine like terms: 30w + 3w = 33w
(18 + 33w + 5w2) = 0

Solving
18 + 33w + 5w2 = 0

Solving for variable 'w'.

Factor a trinomial.
(6 + w)(3 + 5w) = 0

Subproblem 1

Set the factor '(6 + w)' equal to zero and attempt to solve: Simplifying 6 + w = 0 Solving 6 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + w = 0 + -6 w = 0 + -6 Combine like terms: 0 + -6 = -6 w = -6 Simplifying w = -6

Subproblem 2

Set the factor '(3 + 5w)' equal to zero and attempt to solve: Simplifying 3 + 5w = 0 Solving 3 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5w = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5w = 0 + -3 5w = 0 + -3 Combine like terms: 0 + -3 = -3 5w = -3 Divide each side by '5'. w = -0.6 Simplifying w = -0.6

Solution

w = {-6, -0.6}

See similar equations:

| 4t+5=3t+5+t | | z^2+13z=-42 | | 33x=3x^2-7x-18 | | .7(v+3.2)=-.28 | | -14x^2+54x-36=0 | | 3-x(x-5)=5 | | 24k^2-31k-36=k | | 0.6(x-1.3)=.15 | | 27-4t-12t=t-7 | | X^2-5x-29=0 | | 12x+3x=100+22 | | 64=((2*h)*h)/2 | | 5x+5x=70 | | x^2-6-5x=0 | | -8m-3m=16 | | 64=(2h*h)/2 | | 7(4n-5m)= | | (8i)(4i)(9i)= | | 13x^2+44x+14=7x^2 | | (X-5y)(x+3y)= | | y=x^3-81x | | 3x^2-15-2x=0 | | 72=3(3z) | | 9(g-5h)= | | 10x-9y=2 | | 15x+7x-2=0 | | x+x+74=180 | | f(x)=3x^2+5x-7 | | 30=22.5/r | | (7x+3)(2x+6)=0 | | y=-x^2-10x+25 | | 10(b+4c)= |

Equations solver categories